The role of concomitant vitamin D3 and K2 treatment after laminectomy in spinal stenosis surgery of patients with osteoporosis - Emet, Abdulsamet; Demirtas, Yunus (International Journal of Research in Orthopaedics, 2023)
Background: Readmission because of ongoing pain and complaints who undergone spinal surgery with osteoporosis is increasing. This study investigated the efficacy of concomitant vitamin D3 and K2 usage in the surgical treatment of patients with lumbar spinal stenosis who have osteoporosis. The aim of the study was to treatment strategy is to reduce the patient’s low back pain and decrease readmission rates due to ongoing pain. Methods: A total of 22 patients with osteoporosis included in the study who had lumbar decompression via laminectomy surgery with posterior instrumentation for spinal stenosis. Patients were divided into groups according to use additional supplement of vitamin D3+K2. Group 1 was control group who received only vitamin D3 and group 2 was patients who received vitamin D3+K2 treatment. Patients were called to their sixth month check-up and their pre-and post-treatment VAS scores and Roland-Morris scores were filled in and readmission rates due to ongoing pain were compared. Results: 9 male and 13 female participants with a mean age of 64.4 were in the study. The mean T-score in bone mineral density (BMD) was -2.7 in group 1 and -2.6 in group 2. A significant difference was found when the pre-operative and post-operative VAS and RM scores of all patients were compared (p<0.05). The mean readmission rates due to ongoing pain is 4 in group 1 and 7 in group 2. A significant difference was found when readmission rates due to ongoing pain were compared (p<0.05). Conclusions: Concomitant vitamin D3 and K2 usage in the surgical treatment of patients with lumbar spinal stenosis who have osteoporosis is a valuable treatment option to reduce the rate of admission to the hospital because of ongoing pain.